Conceptualisations of writing in the curricula and the teachers' guides of Greek preschool education: a critical discourse analysis. Issue 2 (22nd September 2020) - Tentolouris, Filippos
Abstract : The goal of this article is to explore the conceptualisations of writing in the curricula and the teachers' guides of Greek preschool education (4–6 years of age). Ivanič's framework of the six discourses of writing (the skills discourse, the creativity discourse, the process discourse, the genre discourse, the social practices discourse and the sociopolitical discourse), which shows how writing is framed in literacy education, was used for the exploration of these conceptualisations. A document‐based investigation was conducted in order to collect all the relevant texts concerning early writing and critical discourse analysis was employed in the interest of identifying and relating discourses in two key policy documents focusing on features of vocabulary and propositional assumptions. A discourse of social practices was found in the first document while the same discourse with features of other discourses co‐occur in the second document. Since the relationship among the discourses in the latter text is implicit, specific assumptions should be made to maximise their coherence. Finally, I suggest that although the social practices discourse makes a step forward which has not been conducted decisively at an international level, its implicit relationship with the other discourses and especially with the sociopolitical discourse obstructs the constitution of a comprehensive writing pedagogy.